Branding Strategy in Market Development of Fisheries Sector MSMEs: A Case Study in Kupang City - Tingga, Chairul Pua; Geno, Zainal Arifin Pua (ProBisnis : Jurnal Manajemen, 2024)
This study aims to analyze the branding strategy applied by fishery product processing MSMEs in an effort to increase market share. This research uses a qualitative method with a case study approach in fish floss processing MSMEs. The research subjects were fishery product processing MSMEs, while data collection techniques involved observation and structured interviews. Data analysis was conducted through triangulation. The results showed that the branding strategy implemented by these MSMEs has not succeeded in increasing the market share of their products, because many of them still have not implemented the branding strategy optimally.